General Stress Responses in the Honey Bee - Even, Naïla (Insects, 2012)
The biological concept of stress originated in mammals, where a “General Adaptation Syndrome” describes a set of common integrated physiological responses to diverse noxious agents. Physiological mechanisms of stress in mammals have been extensively investigated through diverse behavioral and physiological studies. One of the main elements of the stress response pathway is the endocrine hypothalamo-pituitary-adrenal (HPA) axis, which underlies the “fight-or-flight” response via a hormonal cascade of catecholamines and corticoid hormones. Physiological responses to stress have been studied more recently in insects: they involve biogenic amines (octopamine, dopamine), neuropeptides (allatostatin, corazonin) and metabolic hormones (adipokinetic hormone, diuretic hormone). Here, we review elements of the physiological stress response that are or may be specific to honey bees, given the economical and ecological impact of this species. This review proposes a hypothetical integrated honey bee stress pathway somewhat analogous to the mammalian HPA, involving the brain and, particularly, the neurohemal organ corpora cardiaca and peripheral targets, including energy storage organs (fat body and crop). We discuss how this system can organize rapid coordinated changes in metabolic activity and arousal, in response to adverse environmental stimuli. We highlight physiological elements of the general stress responses that are specific to honey bees, and the areas in which we lack information to stimulate more research into how this fascinating and vital insect responds to stress.